2015
DOI: 10.2519/jospt.2015.5021
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Low-Load Motor Control Exercises and Education Versus a High-Load Lifting Exercise and Education to Improve Activity, Pain Intensity, and Physical Performance in Patients With Low Back Pain: A Randomized Controlled Trial

Abstract: Study Design Randomized controlled trial. Background Low back pain is a common disorder. Patients with low back pain frequently have aberrant and pain-provocative movement patterns that often are addressed with motor control exercises. Objective To compare the effects of low-load motor control (LMC) exercise and those of a high-load lifting (HLL) exercise. Methods Seventy participants with recurrent low back pain, who were diagnosed with nociceptive mechanical pain as their dominating pain pattern, were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 39 publications
4
84
0
7
Order By: Relevance
“…Only a few previous studies have used periodization and heavy resistance training for LBP (10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have used periodization and heavy resistance training for LBP (10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the effects of motor control exercises on LBP, Aasa et al 49 reported a mean PSFS baseline score of 3.8 and a 2-month follow-up score of 7.8. Similarly, Macedo et al 47 reported a baseline PSFS score of 3.7 and a 2-month follow-up score of 5.9 in patients treated with motor control exercises.…”
Section: Discussionmentioning
confidence: 99%
“…34 The spine is, however, controlled by a complex interplay of many muscles, and this might be the reason why the specific features of exercises, which are addressed in books and research studies, differ. Some approaches highlight exercises targeting the deeper muscles of the trunk, 1 whereas others highlight correction of movement faulty movement pattern.…”
Section: Epidemiologymentioning
confidence: 98%